Karakter Literatur Indonesia tentang al-Qur’ān - Didin Syafruddin (Studia Islamika, 1995)
This article is a review of the book "Popular Indonesian Literature of the Qur'an" by Howard M. Federspiel (Ithaca: Cornell Modern Indonesia Project, Southeast Asia Program, Cornell University, 1994).This book is the first work written by Howard M. Federspiel, professor of political science, Ohio State University. Since his studies at McGill University, the development of Indonesian Islam has become a concern. He wrote his Ph.D. dissertation at the University of the Unity of Islam (Persis), one of the Indonesian Islamic reformist organizations that emphasize movement purification. Numerous works have also been published in various scientific journals with regard to the issue of Islam in modern Indonesia. Among these "Sukarno and His Muslim apologist", "The Political and Social Language of Indonesian Muslims: The Case of Al-Moslem", "An Introduction to Qur'anic Commentaries in Contemporary Southeast Asia". His work is still relatively new Muslim Intellectual and National Development in Indonesia. While the Popular Indonesian Literature of the Qur'an which will be discussed below is his latest work.DOI: 10.15408/sdi.v2i2.839